Corporate friction : how corporate law impedes American progress and what to do about it / David Yosifon, Santa Clara Law School. - Yosifon, David G., 1973- (Cambridge University Press, 2018)
Corporate law in the United States requires directors to manage firms in the interests of shareholders, which means never sacrificing profits in service of other stakeholders or interests. In this timely, groundbreaking book, David Yosifon argues that this rule of 'shareholder primacy' is logically, ethically, and practically unsound, and should be replaced by a new standard that compels directors of our largest corporations to manage firms in a socially responsible way. In addition to summarizing existing debates on the issue - and giving special attention to the Supreme Court's decision in Citizens United - Yosifon explores the problem of corporate patriotism and develops a novel approach to the relationship between corporate law and consumer culture. The book's technical acumen will appeal to experts, while its engaging prose will satisfy anyone interested in what our corporate law does, and what it should do better.